Development of visual perception test for children aged 3-8 years (Research, Society and Development, 2020)
Eyesight is an essential sense. The eyes are responsible for 80% of the information we receive about the world around us. The ability to perceive visual stimuli should therefore be considered the most effective ability when compared to other senses. Furthermore, it predisposes all developmental and growth issues in children. Impairment in visual perception leads to several problems, such as learning disorders, behavioral disorders, emotional problems and social disorders. Visual perception impairment is also often comorbid with other disabilities. Using the Frostig test, the examination of visual perception has begun to be carried out by several health workers, such as psychologists and occupational therapists. Although the Frostig test has been used in Indonesia, some of its aspects need to be reviewed. Indonesia’s visual perception tests are limited, and infrequently inspected. This study aims to modify the Frostig test into a testing instrument that is appropriate to the culture of child development in Indonesia and to be a child-friendly instrument, especially for children aged three-to-eight years. Modifications that will be made include the amendment of item content, additional dimensions, items and response options. The measurement of content validity involved 20 participants, a trial test of 30 participants, a visual attention test of 111 participants and a test for validity and reliability in 219 participants. The exploratory factor analysis confirmed six sub-tests, consisting of 38 items, with composite reliabilities ranging from 0.648-0.823.